The Great Indian Road: India – Central Asia – Transcaucasia - Rtveladze, Eduard V. (Anabasis. Studia Classica et Orientalia, 2010)
The Great Silk Road which in ancient times linked the countries of the Far East with the Mediterranean area by way of Central Asia is well known to the learned and general public. Much less known is the other great trade road, also through Central Asia, that ran from India to the Mediterranean shores. Unlike the Silk Road with its predominantly overland routes, the road from India was a compound of land and waterway routes. This road started from Taxila, the capital of Gandhara, in north-western India, and crossed the Hindu Kush range into Baktria. After this it followed the Kokcha, Kunduz Darya, and Balkhab rivers to the Oxus (Amu Darya), and then down the Oxus toward Chorasmia. At Amul, or Chardzhou, a route branched off towards Margiana, Parthyene and the Atrek valley. From Chorasmia the main route continued along the Uzboi channel to the Caspian Sea, and crossing the sea, passed on to the mouth of the Kura river (ancient Cyrus); thence along the river and through modern Azerbaijan (Caucasian Albania) and eastern Georgia (Ancient Iberia) it crossed the Surami Pass to reach the valley of the Rioni river (ancient Phasis). In the lower course of the Phasis (western Georgia, legendary Colchis) was situated a city bearing the same name and inhabited by people of various nationalities, including Baktrians and Indians. Thence by the Euxine the road led to the Greek cities of the Black Sea region and so ultimately to South-East Europe. The available data indicate the importance of the Great Indian Road, and calls for the need for further profound and thorough study of the history of the formation and the operation of this great thoroughfare on the basis of archaeological, literary, and other sources.